Implementasi Kebijakan Rencana Tata Ruang Wilayah (RTRW) Dalam Mewujudkan Ruang Terbuka Hijau (RTH) Publik di Kota Tangerang Selatan - Muhamad Hafiz; Ayuning Budiati; Rina Yulianti (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2022)
This research focuses on the Implementation of Regional Spatial Planning Policy in Fulfillment of Green Open Space in South Tangerang City. The aim of the research is to find out how the Implementation of Regional Spatial Planning Policy in Creating Green Open Space in South Tangerang City. The theory of policy implementation from Van Metter and Van Horn, namely policy standards and objectives, resources, characteristics of implementing organizations, inter-organizational communication, dispositions or attitudes of implementers and the social, political and economic environment. The research method used is descriptive qualitative method. The results of the research show that (1) the standards and policy objectives are not optima, (2) the resources are quite optimal, (3) the characteristics of the organization implementing the green open space policy are less than optimal, (4) the communication of implementing organizations is good, (5) the disposition or attitude of the executors is still not optimal, (6) the social, political and economic environment of green open space policies is less than optimal marked by the lack of support from the political elite for regional spatial planning policies in fulfilling green open spaces in South Tangerang City.